KADAR HORMON AUKSIN PADA TANAMAN KENAF (Hibiscus cannabinus L.) BERCABANG DAN TIDAK BERCABANG - Yunin Hidayati (Agrovigor, 2009)
Kenaf is one of fiber producing plants. According to the existence of branches, kenaf is classified into two group, consisting of: kenaf with branch and with no branch.Morphology observation, consist of the height of plant, the number of node, the number of branch and the length of branch was observed. The morphology observation showed that there were differences morphological characters, including of the height of plant, the number of node, the length of branch, and the number of node more branching kenaf, control non branching (KR11) and control branching (SM004).Non branching plants (KR11) have the highest habitus and smallest number of branch compare to other groups. Control branching (SM004) was the shortest habitus and greatest number of branch compare to other group. The highest of Non branching plants (KR11) 230,6 ± 36,7 cm and the smallest control branching (SM004) 116,3 ± 64,4 cm. The greatest number of branch found in controled branch SM004, with 5,6 ± 2,7 branch in every plant and the smallest is KR11 with 0,8 ± 0,8 branch in every plant.According to this research the length of plant influence the branch. The highest level of auxin were in the shoot tip and the lowest level were in root tip. The higher auxin will produce less branch, the lower auxin will produce more branch.